FACTORS AFFECTING HAND WASHING PRACTICE AMONG ELEMENTARY SCHOOLS STUDENTS IN INDONESIA - Nazliansyah Nazliansyah; Susheewa Wichaikull; Kanokwan Wetasin (Belitung Nursing Journal, 2016)
Background: Hand washing is the most effective method of preventing the transmission of diseases through hands. Objective: To identify relationships between gender, availability of hand washing facilities, perception of barriers toward hand washing compliance and subjective norm in implementing hand washing practice among students of public elementary school in Belitung district, Indonesia. Method: A cross-sectional research study was used in this study. Of 309 participants were recruited in 11 public elementary schools from 3 sub districts that has been implemented the hand washing program in Belitung, Indonesia. Purposive sampling method was used to select the participants. This study was used a self-administered questionnaire with minimal interference in order to minimize bias and by emphasizing to the students that this is not an examination. Results: The results showed that 71.8% of the students were not hand washing properly. It also showed that availability of hand washing facilities and gender were not related with hand washing behavior. In regards of barrier perception toward hand washing compliance also showed that was not related to hand washing practice among elementary schools’ students. However, subjective norm (c² =4.459, p < .05) was related to hand washing practice among elementary schools’ students. Conclusion: Subjective norm has a significant relationship to hand washing behavior. Thus, health care provider could develop specific intervention programs based on TPB to promote subjective norm among elementary schools’ students since this norm or perception of norm can motivate hand washing behavior among the students effectively.